2010
DOI: 10.1108/17471111011051757
|View full text |Cite
|
Sign up to set email alerts
|

Hotel employees' beliefs on unethical behavior

Abstract: PurposeThe purpose of this study is to explore the beliefs of employees who work in different positions in the hotels in Edirne, Turkey regarding unethical applications.Design/methodology/approachThe survey method was used to determine the hotel personnel's unethical behaviors in the process of the service operation in hotels. The questionnaire was mainly developed from a Varinli study which was applied to the employees' job‐related ethics.FindingsThe findings have been evaluated and analyzed using the SPSS 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Furthermore, employee belief signifies the sense of pride and commitment that individuals hold toward their work and the organization. It represents their emotional attachment and dedication to their job and the organization's success, as emphasized by Gonenc et al (2010).…”
Section: Employee Beliefmentioning
confidence: 99%
“…Furthermore, employee belief signifies the sense of pride and commitment that individuals hold toward their work and the organization. It represents their emotional attachment and dedication to their job and the organization's success, as emphasized by Gonenc et al (2010).…”
Section: Employee Beliefmentioning
confidence: 99%
“…Internal control system factor was measured with five items from Ahmad and Norhashim (2008). And finally Attitude to stealing factor was measured with five items modified from the study of Kallier et al (2013), Intention to stealing was measured with five items from Moorthy et al (2015), and Stealing behavior was measured with four items from the study of Gonenc and Yukselen (2010). All of the above items were measured based on a seven-point Likert scale ranging from 1 = strongly disagree, 7 = strongly agree.…”
Section: Questionnaire Surveymentioning
confidence: 99%
“…Such a practice is known as greenwashing. Research on service workers’ greenwashing behavior in the hospitality industry is still rare, although it has been found that workers may adopt greenwashing behaviors when they are equipped with products that are not environmentally friendly (Guler & Yukselen, 2010), such as those making misleading claims about using environmentally friendly materials (Pizam, 2009). Employees who experience psychological contract fulfillment have been found to have an increase in perceived obligations to their employers, and, in extreme cases, employees may seek to repay their employers by engaging in pro-organizational behavior (Fleischman et al, 2019).…”
Section: Introductionmentioning
confidence: 99%